2014
DOI: 10.7314/apjcp.2014.15.20.8623
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NUF2 Inhibits Tumor Growth and Induces Apoptosis in Human Hepatocellular Carcinomas

Abstract: Background: As an important component of the NDC80 kinetochore complex, NUF2 is essential for kinetochore-microtubule attachment and chromosome segregation. Previous studies also suggested its involvement in development of various kinds of human cancers, however, its expression and functions in human hepatocellular carcinoma (HCC) are still unclear. Materials and Methods: In the present study, we aimed to test the hypothesis that NUF2 is aberrant in human HCCs and associated with cell growth. Results: Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…15 Here, we further demonstrated the high NUF2 expression is significantly associated with poorer HCC patient survival, and NUF2 is a promising prognostic biomarker to accurately predict early HCC recurrence postsurgical resection. We further evaluated the prognostic biomarker potential of the transcriptome signature in an independent cohort and identified NUF2 as a promising biomarker to predict HCC early recurrence.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…15 Here, we further demonstrated the high NUF2 expression is significantly associated with poorer HCC patient survival, and NUF2 is a promising prognostic biomarker to accurately predict early HCC recurrence postsurgical resection. We further evaluated the prognostic biomarker potential of the transcriptome signature in an independent cohort and identified NUF2 as a promising biomarker to predict HCC early recurrence.…”
Section: Introductionmentioning
confidence: 56%
“…Previous evidence demonstrated that NUF2 promotes cell growth and inhibits apoptosis in HCC cells. 15 Here, we further demonstrated the high NUF2 expression is significantly associated with poorer HCC patient survival, and NUF2 is a promising prognostic biomarker to accurately predict early HCC recurrence postsurgical resection.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…For example, elevated NUF2 gene expression has been found in a range of tumor types and cell lines (23)(24)(25)(26) and is associated with poor outcome in cancer patients (23,25). Furthermore, silencing of NUF2 inhibits tumor growth and leads to apoptosis in cancer cell lines (23)(24)(25)(26)(27)(28), likely induced by the spindle checkpoint pathway (22). Experimental follow-up is required to ultimately understand the role of the clustered NUF2 mutations in cancer.…”
Section: Significancementioning
confidence: 99%
“…Both of these proteins are known cancer drug targets and are now being considered as crucial molecules in the development of tumor-agnostic drugs to treat diverse cancer types 45 . Silencing of the NUF2 protein has been shown to hinder tumor growth across cancer types 46 www.nature.com/scientificreports www.nature.com/scientificreports/ NTRK1 protein has been successfully targeted by the drug Entrectinib 48 . Our results, therefore, suggest that the drug Entrectinib may be a choice in the treatment regimen of a diverse number of cancer types but may not be beneficial to patients diagnosed with STES, BLCA, LUSC (apart from ROS1-positive) and PRAD.…”
Section: Resultsmentioning
confidence: 99%